Hsp90 and hepatobiliary transformation during sea lamprey metamorphosis - Chung-Davidson, Yu-Wen (BMC Dev Biol, 2015)
BACKGROUND: Biliary atresia (BA) is a human infant disease with inflammatory fibrous obstructions in the bile ducts and is the most common cause for pediatric liver transplantation. In contrast, the sea lamprey undergoes developmental BA with transient cholestasis and fibrosis during metamorphosis, but emerges as a fecund adult. Therefore, sea lamprey liver metamorphosis may serve as an etiological model for human BA and provide pivotal information for hepatobiliary transformation and possible therapeutics. RESULTS: We hypothesized that liver metamorphosis in sea lamprey is due to transcriptional reprogramming that dictates cellular remodeling during metamorphosis. We determined global gene expressions in liver at several metamorphic landmark stages by integrating mRNA-Seq and gene ontology analyses, and validated the results with real-time quantitative PCR, histological and immunohistochemical staining. These analyses revealed that gene expressions of protein folding chaperones, membrane transporters and extracellular matrices were altered and shifted during liver metamorphosis. HSP90, important in protein folding and invertebrate metamorphosis, was identified as a candidate key factor during liver metamorphosis in sea lamprey. Blocking HSP90 with geldanamycin facilitated liver metamorphosis and decreased the gene expressions of the rate limiting enzyme for cholesterol biosynthesis, HMGCoA reductase (hmgcr), and bile acid biosynthesis, cyp7a1. Injection of hsp90 siRNA for 4 days altered gene expressions of met, hmgcr, cyp27a1, and slc10a1. Bile acid concentrations were increased while bile duct and gall bladder degeneration was facilitated and synchronized after hsp90 siRNA injection. CONCLUSIONS: HSP90 appears to play crucial roles in hepatobiliary transformation during sea lamprey metamorphosis. Sea lamprey is a useful animal model to study postembryonic development and mechanisms for hsp90-induced hepatobiliary transformation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12861-015-0097-2) contains supplementary material, which is available to authorized users.